MODERNISASI POLA SISTEM PENDIDIKAN PESANTREN (Studi Kasus Pondok Pesantren Modern Daarul Fikri Mulyoagung Dau Malang) - Setiawan, Eko (ULUL ALBAB Jurnal Studi Islam, 2013)
Pesantren is a native Indonesian educational institutions that have a strong tradition of roots within the community. In the era of modernization or the advancement of science and technology today, pesantren education system to be maintained. The purpose of this study to determine the model of modernization of education pesantren, pesantren education plus minus modernization, modern pesantren patterns. In this study, a type of qualitative research which uses a case study model. Data collection techniques used participant observation, in-depth interviews, documentary studies, the data analysis process begins by reviewing all available data from various sources, namely interviews, observation, which has been written in the field notes, personal papers, official documents, images, etc. From the analysis, the authors conclude that the modernization undertaken Pesantren Daarul Fikri is very different from the other Islamic pesantren in Indonesia. Pesantren Daarul Fikri has imposed a very strict curriculum. Students must follow all the rules in regular education and obedient. The curriculum combines Daarul Fikri trying to learn classical tradition with modern style is embodied in both the teaching and learning system.